BIBLIOMETRIC ANALYSIS OF THRIFTING RESEARCH IN MARKETING MANAGEMENT: MAPPING INTELLECTUAL STRUCTURE AND FUTURE RESEARCH AGENDA - Nur Eli Zayati; Suharto; Rachmad Ilham (STMIK Indonesia Banda Aceh, 2026)
This study maps the development of thrifting research in marketing management using quantitative bibliometric analysis on the Scopus database for the period 2015-2025. Quantitative methods are used to statistically measure publication trends , researcher productivity , and research structure . The results show significant growth since 2020 with an average of 23.5 percent per year . Four dominant themes were identified : consumer behavior , marketing strategy , environmental sustainability , and digital business models. The United States dominates with 32.4 percent of publications , while Indonesia only has 1.8 percent . Thrifting consumers prioritize product uniqueness over price. Knowledge gaps include a lack of research from the perspective of business actors . This study provides a statistical data -based map as a reference for future research development .